Simultaneous multislice accelerated TSE for improved spatiotemporal resolution and diagnostic accuracy in magnetic resonance neurography: a feasibility study - Preisner, Fabian; Hayes, Jennifer; Charlet, Tobias; Carinci, Flavio; Hielscher, Thomas; Schwarz, Daniel; Vollherbst, Dominik; Breckwoldt, Michael O.; Jesser, Jessica; Heiland, Sabine; Bendszus, Martin; Hilgenfeld, Tim (Investigative radiology, 2023)
Objectives - This study aims to evaluate the utility of simultaneous multislice (SMS) acceleration for routine magnetic resonance neurography (MRN) at 3 T. - Materials and Methods - Patients with multiple sclerosis underwent MRN of the sciatic nerve consisting of a standard fat-saturated T2-weighted turbo spin echo (TSE) sequence using integrated parallel acquisition technique (PAT2) acceleration and 2 T2 TSE sequences using a combination of PAT-SMS acceleration (1) to reduce scan time (PAT2-SMS2; SMS-TSEFAST) and (2) for time neutral increase of in-plane resolution (PAT1-SMS2; SMS-TSEHR). Acquisition times were 5:29 minutes for the standard T2 TSE, 3:12 minutes for the SMS-TSEFAST, and 5:24 minutes for the SMS-TSEHR. Six qualitative imaging parameters were analyzed by 2 blinded readers using a 5-point Likert scale and T2 nerve lesions were quantified, respectively. Qualitative and quantitative image parameters were compared, and both interrater and intrarater reproducibility were statistically assessed. In addition, signal-to-noise ratio/contrast-to-noise ratio (CNR) was obtained in healthy controls using the exact same imaging protocol. - Results - A total of 15 patients with MS (mean age ± standard deviation, 38.1 ± 11 years) and 10 healthy controls (mean age, 29.1 ± 7 years) were enrolled in this study. CNR analysis was highly reliable (intraclass correlation coefficient, 0.755-0.948) and revealed a significant CNR decrease for the sciatic nerve for both SMS protocols compared with standard T2 TSE (SMS-TSEFAST/SMS-TSEHR, −39%/−55%; P ≤ 0.01). Intrarater and interrater reliability of qualitative image review was good to excellent (κ: 0.672-0.971/0.617-0.883). Compared with the standard T2 TSE sequence, both SMS methods were shown to be superior in reducing pulsatile flow artifacts (P < 0.01). Ratings for muscle border sharpness, detailed muscle structures, nerve border sharpness, and nerve fascicular structure did not differ significantly between the standard T2 TSE and the SMS-TSEFAST (P > 0.05) and were significantly better for the SMS-TSEHR than for standard T2 TSE (P < 0.001). Muscle signal homogeneity was mildly inferior for both SMS-TSEFAST (P > 0.05) and SMS-TSEHR (P < 0.001). A significantly higher number of T2 nerve lesions were detected by SMS-TSEHR (P ≤ 0.01) compared with the standard T2 TSE and SMS-TSEFAST, whereas no significant difference was observed between the standard T2 TSE and SMS-TSEFAST. - Conclusions - Implementation of SMS offers either to substantially reduce acquisition time by over 40% without significantly impeding image quality compared with the standard T2 TSE or to increase in-plane resolution for a high-resolution approach and improved depiction of T2 nerve lesions while keeping acquisition times constant. This addresses the specific needs of MRN by providing different imaging approaches for 2D clinical MRN.